Air Quality and Social Vulnerability: Estimating Mining-Induced PM10 Pollution in Tula, Mexico - Osiel O. Mendoza-Lara; Andrés O. López-Pérez; Claudia Yazmín Ortega-Montoya; Adria Imelda Prieto Hinojosa; J. M. Baldasano (Atmosphere, 2025)
The Tula Metropolitan Area in Mexico is characterized by significant industrial activity, including thermoelectric power plants, refineries, cement plants, and mining operations. While the impact of mining on air quality has been less studied compared to other industries, this research aims to estimate the contribution of mining areas to PM10 air pollution in the region. Using the AERMOD dispersion model coupled with the WRF meteorological model, emission areas were identified through GIS analysis, and specific emission factors for mining activities were applied. The results indicate that mining areas can contribute up to 40 µg/m3 of PM10, exceeding both national and international air quality standards. Monitoring data suggests that mining activities account for approximately 30% of the measured PM10 concentrations in the area. Furthermore, spatial analysis using the Urban Marginalization Index (UMI) revealed that areas with high PM10 concentrations often coincide with regions of high social vulnerability, particularly in communities with elevated levels of marginalization. This study concludes that mining operations significantly contribute to air pollution in the Tula Metropolitan Area, highlighting the need for targeted mitigation measures and public policies that address both environmental and social vulnerabilities.